THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON TEACHER PERFORMANCE MEDIATED BY JOB SATISFACTION IN ELEMENTARY SCHOOLS - Samsu Bahtiar; Lutfi Nur; Sandra Arhesa (Universitas Majalengka, 2026)
Teacher performance is one of the key factors in improving the quality of education. One factor believed to influence teacher performance is the principal’s transformational leadership, both directly and through increased teacher job satisfaction. This study aims to analyze the effect of transformational leadership on teacher job satisfaction and performance and to examine the role of job satisfaction as a mediating variable. The study employs a quantitative approach using a descriptive-verificative method. The sample consists of 76 elementary school teachers in Panjalu Subdistrict, Ciamis Regency, selected using a saturation sampling technique. Data were collected via a questionnaire and analyzed using path analysis. The results indicate that both transformational leadership and teacher job satisfaction fall into the high category. Transformational leadership was found to have a positive and significant effect on both teacher job satisfaction and performance. Furthermore, job satisfaction also had a positive and significant effect on teacher performance and acted as a mediator in the relationship between transformational leadership and teacher performance. These findings suggest that the implementation of transformational leadership by school principals can enhance teachers’ job satisfaction, which ultimately leads to improved teacher performance.